Marind Indigenous Ecological Justice: Laudato Si' And Ecological Resilience Facing Industrial Expansion In Merauke, South Papua - Sarang, Rikardus Kristian; Wea, Donatus; Gaol, Erly Lumban; Pudjiarti, Emiliana Sri (GoAcademica Research & Publishing, 2024)
This research analyzes the values of natural harmony in the cosmology of the Marind people of South Papua. The research object was carried out on LMA Marind and priests in the Merauke Archdiocese using a qualitative approach. The findings explain that deforestation due to the conversion of natural forests into large plantations in Merauke, South Papua has threatened the socio-cultural survival of the Marind tribe. The loss of forests as a basis for their ecological and spiritual adaptation is contrary to the principles of ecological justice and environmental sustainability in Laudato Si. Pope Francis emphasized that the earth is the common home of humanity which must be protected for the benefit of all generations. Inclusive development policy reform is needed in Merauke by meeting the needs of indigenous communities and restoring natural habitats as the main orientation, not just the interests of investors. Also, political empowerment of local communities to have control over their customary lands. Harmonization of nature conservation, the human rights of indigenous peoples, and the sustainability of cultural heritage are key amidst investment expansion. Full involvement of the indigenous Marind tribe with high understanding and responsibility is a requirement for ecological-socio-cultural sustainability in Merauke. Marind traditional ecological findings, 1) connectedness with the universe, 2) ecology is part of ancestral traditions and wisdom, 3) ecology is the balance of the ecosystem, 4) ecology is dependence on rivers and seas, 5) ecology is a connection with the supernatural.